2018
DOI: 10.1007/s12325-017-0657-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Low Bone Mineral Density with Anti-Citrullinated Protein Antibody Positivity and Disease Activity in Established Rheumatoid Arthritis: Findings from a US Observational Cohort

Abstract: IntroductionTo assess the relationship between low bone mineral density (BMD), anti-cyclic citrullinated peptide-2 (anti-CCP2) antibodies, and disease activity in patients with established rheumatoid arthritis (RA).MethodsPatients enrolled in a single-center, observational cohort registry of patients with RA. Eligible patients had known BMD, as measured by digital X-ray radiogrammetry (DXR–BMD), and anti-CCP2 antibody measurements at the same time point or within 6 months. Anti-CCP2–immunoglobulin (Ig)G-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
2
7
0
1
Order By: Relevance
“…This indicates that there was a correlation between disease activity and bone loss. Bone mineral density loss occurs in the early stage of RA and increases with the increase of disease activity, which is consistent with the research viewpoints of many scholars [ 16 , 17 ]. Research shows that the CRP and ESR values of the osteoporosis groups were higher than the non-osteoporosis group, and there was a moderate correlation with osteoporosis, but CRP and ESR were not independent predictors of osteoporosis; the research of Tomizawa and other scholars also confirm this point [ 18 ].…”
Section: Discussionsupporting
confidence: 89%
“…This indicates that there was a correlation between disease activity and bone loss. Bone mineral density loss occurs in the early stage of RA and increases with the increase of disease activity, which is consistent with the research viewpoints of many scholars [ 16 , 17 ]. Research shows that the CRP and ESR values of the osteoporosis groups were higher than the non-osteoporosis group, and there was a moderate correlation with osteoporosis, but CRP and ESR were not independent predictors of osteoporosis; the research of Tomizawa and other scholars also confirm this point [ 18 ].…”
Section: Discussionsupporting
confidence: 89%
“…Sabbagh et al [31] found that the inadequate Vitamin D status has a considerably strong association with disease activity in RA cases, and active RA with anti-CCP positivity was associated with lower BMD [32]. Our nding was similar partially, which indicated the need for proper evaluation of Vitamin D status in these patients to ensure the intake of the recommended amount of Vitamin D, but positive anti-CCP was not associated with bone loss in our study.…”
Section: Discussionsupporting
confidence: 75%
“…Regarding this topic, there is evidence that measurement of BMD by dual X-ray radiogrammetry (DXR) at metacarpal diaphysis in the non-dominant hand of RA patients is associated with disease progression, appearance of bone erosions and even, in some studies, with increased mortality (84,85). In addition, DXR is a very sensitive procedure to detect loss of BMD in the hand, which in long-standing RA has been associated with high titers of autoantibodies, mainly ACPA, radiographic progression and the appearance of erosions (86).…”
Section: Bone Mineral Density As Possible Severity Marker In Ramentioning
confidence: 99%